First-principles computations of YxGa1−x As-ternary alloys: a study on structural, electronic, optical and elastic properties - Touam, S.; Belghit, R.; Mahdjoubi, R.; Megdoud, Y.; Meradji, Hocine; Khan, Muhammad Shehryar; Ahmed, Rashid; Khenata, Rabah; Ghemid, Sebti; Rai, Dibya Prakash; Al-Douri, Yarub (Springer Verlag, 2020)
In this work, the first-principles computational study on the structural, elastic, electronic and optical properties of Y xGa 1 - xAs as a function of yttrium concentration (x) is presented. The computations are performed using the full-potential linearized augmented plane wave plus local orbital method designed within density functional theory. Firstly, we performed our calculations on the most stable phases, NaCl and zinc blende, then their transition pressure for each concentration is determined and analysed. Our computed results for the zero yttrium concentration are found consistent with the available experimental measurements as well as with theoretical predictions. Moreover, the dependencies of these parameters upon yttrium concentration (x) were found to be non-linear. We also report computed results on electronic-band structure, electronic energy band gap results and density of states. A systematic study on optical properties to analyse its optoelectronic character and elastic properties is presented. © 2019, Indian Academy of Sciences.